Vena Caval Reconstruction During Postchemotherapy Retroperitoneal Lymph Node Dissection for Metastatic Germ Cell Tumor - Ehrlich, Yaron; Kedar, Daniel; Zelikovski, Avigdor; Konichezky, Miriam; Baniel, Jack (Urology (Ridgewood, N.J.), 2009)
We present our experience with inferior vena cava (IVC) reconstruction in patients undergoing post-chemotherapy retroperitoneal lymph node dissection (PC-RPLND) due to metastatic germ cell tumor. Four patients underwent IVC reconstruction with a prosthetic graft. Early postoperative leg edema was prevented in all 4. Long-term graft patency was maintained in 3 patients, who remained free of chronic venous disorders for a median follow-up of 19 months (range of 13-55 months). In a fourth patient, graft occlusion was noted during follow up, caused by compression of the graft by a recurrent tumor. We conclude that when resection of the IVC is indicated during PC-RPLND, replacement by a prosthetic graft may prevent immediate postoperative leg edema and later chronic venous insufficiency.